Rediscovery and revalidation of the Brazilian endemic Vanilla schwackeana Hoehne (Orchidaceae): its distribution and phylogenetic position - Pansarin, Emerson R. (Plant ecology and evolution, 2024)
Background and aims – With 40 species, Brazil is the centre of diversity for Vanilla . Frederico Carlos Hoehne described eight Vanilla species for the Brazilian flora, including Vanilla schwackeana , an obscure taxon currently assumed to be a synonym of V. planifolia . While studying Neotropical Vanilla , plants were found in gallery forests of the Vale do Rio Doce region, Minas Gerais, south-eastern Brazil. Based on the examination of the protologues of the Brazilian species, in addition to the study of herbarium specimens, it was verified that the plants correspond to the rare V. schwackeana . Material and methods – A redescription of V. schwackeana is provided, and a morphological comparison with other Neotropical taxa is presented. An illustration of V. schwackeana based on living specimens is provided, and its geographic distribution is presented based on recent findings. The position of V. schwackeana within Vanilla is discussed based on both morphological data and a molecular phylogeny. Key results – Vanilla schwackeana is distinguishable by its pseudopetiolate leaves, by its largely elliptic to obelliptic leaf blades with attenuate base and acuminate apex, by its apical racemes with small flowers, by its yellow labellum with white undulate-crenulate margins, and by its papillous appendages on the apical portion of the labellar crest. Both morphological and molecular data suggest a close relationship of V. schwackeana with V. appendiculata , V. hartii , and the Brazilian endemic V. rupicola . Based on current data, V. schwackeana is assessed as Critically Endangered. Conclusion – Integrative taxonomy was crucial to understand the identity and species boundaries of V. schwackeana . The V. appendiculata/V. schwackeana /( V. hartii / V. rupicola ) clade comprises an unrecognized infrageneric Vanilla group. It seems plausible that the formation of a new infrageneric group will be necessary. As the habitat of V. schwackeana has been devastated by iron ore extraction, conservation strategies for this Brazilian endemic species will be necessary.